User Satisfaction-Driven Requirement Mapping for Learning Management Systems in Higher Education: A PLS-SEM Approach - Muhammad Fahmi Alby; Muharman Lubis; Luthfi Ramadani (Journal of Business, Social and Technology, 2026)
Background: The widespread adoption of Learning Management Systems (LMSs) in higher education has intensified the need for systematic, user-centered system evaluation. Despite the growing utilization of LMSs, few studies have simultaneously integrated psychological, cognitive, and technical factors into a unified requirement-mapping framework. Objective: This study investigates the determinants of LMS user satisfaction in higher education using six constructs: Expectation of Quality, Software Adequacy, Feature Interactivity, Cognitive Presence, Computer Self-Efficacy, and Time Management. Methods: A quantitative survey was employed to collect data from 132 students and 83 lecturers. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS, with 5,000-subsample bootstrapping. Results: Expectation of Quality (β = 0.312), Feature Interactivity (β = 0.284), Software Adequacy (β = 0.347), and Time Management (β = 0.198) showed significant positive effects on user satisfaction. Cognitive Presence (β = −0.164) and Computer Self-Efficacy (β = −0.128) exhibited significant negative relationships with user satisfaction. A requirement-mapping model was developed using the MoSCoW prioritization approach. Conclusion: LMS user satisfaction is primarily driven by system quality, feature interactivity, and time management. The integrated technical–psychological model offers a practical framework for user-centered LMS design and development prioritization.